Strategies for Environmental Education on Renewable Energy through the Study of Social Representations - Remmas, Rachidazohra; Hakem, Oumdjillali; Tewfik, Tamma (Journal of Ecohumanism, 2025)
This article explains a psycho-pedagogical approach that aims to develop students’ social skills in the field of renewable energies. This approach moves beyond the acquisition of knowledge and technical skills to focus on interpersonal skills. It does so by articulating cognitive and emotional dimensions through the study of students’ social representations of renewable energies.This study is based on the structural approach, specifically the central core theory. It made it possible to identify the importance of key elements, namely solar energy and oxygen. These elements can therefore be mobilized in the design of an educational project aimed at developing social competence related to sustainable development issues and renewable energies.